2004
DOI: 10.1161/01.str.0000122622.73916.d2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Quantitative EEG in Acute Ischemic Stroke With 30-Day NIHSS Score

Abstract: Background and Purpose-Magnetic resonance imaging (MRI) methods such as diffusion-(DWI) and perfusion-weighted (PWI) imaging have been widely studied as surrogate markers to monitor stroke evolution and predict clinical outcome. The utility of quantitative electroencephalography (qEEG) as such a marker in acute stroke has not been intensively studied. The aim of the present study was to correlate ischemic cortical stroke patients' clinical outcomes with acute qEEG, DWI, and PWI data. Materials and Methods-DWI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(164 citation statements)
references
References 16 publications
7
154
3
Order By: Relevance
“…Th e addition of EEG data improved the predictive value to 85% (for both raw and quantitative EEG) [24]. Th e acute delta change index correlates with 30-day NIHSS as accurately as initial mean transit time on MRI and actually better than initial DWI volume (emphasizing the link between qEEG parameters and blood fl ow) [35]; other parameters such as the delta/alpha ratio and the relative alpha percentage also correlate with the 30-day NIHSS [34]. As early as 6 hours after stroke, the pdBSI correlates with the 1-week NIHSS.…”
Section: Quantitative Eeg In Ischemiamentioning
confidence: 94%
See 1 more Smart Citation
“…Th e addition of EEG data improved the predictive value to 85% (for both raw and quantitative EEG) [24]. Th e acute delta change index correlates with 30-day NIHSS as accurately as initial mean transit time on MRI and actually better than initial DWI volume (emphasizing the link between qEEG parameters and blood fl ow) [35]; other parameters such as the delta/alpha ratio and the relative alpha percentage also correlate with the 30-day NIHSS [34]. As early as 6 hours after stroke, the pdBSI correlates with the 1-week NIHSS.…”
Section: Quantitative Eeg In Ischemiamentioning
confidence: 94%
“…Several parameters correlate with initial stroke severity as measured by the National Institutes of Health Stroke Scale (NIHSS) in both the acute (brain symmetry index [BSI]) [19,31] and subacute periods (relative alpha percen tage, relative alpha-beta percentage, relative delta-theta percentage, delta/alpha ratio, delta-theta/alpha-beta ratio, and global pairwise derived BSI [pdBSI]) [32][33][34]. qEEG parameters correlate with the volume of infarc tion on MRI, such as the acute delta change index [35], global pdBSI [32], relative alpha percentage, relative alpha-beta percentage, relative delta-theta percentage, delta/alpha ratio, and delta-theta/alpha-beta ratio [36]. In the case of subcorti cal infarcts, both the delta-theta/alpha-beta ratio and the pdBSI correlate surprisingly well with infarct volumes, possibly related to the consequences of diaschisis on CBF in lacunar brainstem infarcts [33,36].…”
Section: Quantitative Eeg In Ischemiamentioning
confidence: 99%
“…Measuring the rate of change in average delta power yields a modest correlation with volume of initial mean transit time (r00.79; p<0.01), follow-up diffusion-weighted imaging volume (0.62; p< 0.05), and 30-day National Institutes of Health Stroke Scale (NIHSS) score (r 00.80; p < 0.01) [112]. Subsequent quantitative EEG measures (subacute delta-alpha power ratio and relative alpha power) strongly correlated with 30-day NIHSS (r00.91; p<0.001 and r00.82; p<0.01, respectively) [113].…”
Section: Usefulness In Ischemic Stroke Monitoringmentioning
confidence: 99%
“…Prior studies have demonstrated that EEG changes can be seen with brain that is underperfused [13][14][15]. Actually, with decreasing perfusion sequential EEG changes are observed while brain tissue initially is in a state of reversible and then later irreversible brain injury [16].…”
mentioning
confidence: 99%